Pengaruh Kualitas Pelayanan, Sosialisasi, dan Sanksi terhadap Kepatuhan Wajib Pajak dalam Membayar Pajak Kendaraan Bermotor di Kota Batam - Nababan, Dorasi Yulidia; Janrosl, Viola Syukrina E (Masyarakat Ekonomi Syariah Bogor, 2024)
This study aims to analyze the effect of service quality, socialization and sanctions on taxpayer compliance in paying motor vehicle taxes in Batam City. This study uses a descriptive and quantitative statistical approach with a population of 442,092 motorized vehicle taxpayers in Batam City. Sampling in this study was by using a random sampling technique using the slovin formula, totaling 100 respondents and using a questionnaire as a data collection instrument. The results of this study are that partially service quality affects taxpayer compliance. Socialization partially affects taxpayer compliance, and sanctions partially affects taxpayer compliance. Quality of service, outreach, and sanctions simultaneously affect taxpayer compliance.